Determining Physical Fitness for PPLOP Basketball Athletes in Central Java using Sport-specific Test and Measurement - Agam Akhmad Syaukani; Nur Subekti; Eko Sudarmanto (JUARA : Jurnal Olahraga, 2020)
The level of physical condition can directly affect the team's success in winning the match. The purpose of this study is to implement sport-specific test and measurement related to basketball to investigate the level of fitness for basketball athletes in Central Java highschool basketball team (PPLOP). The total of 13 athletes were signed for this study. Methods used to collect data were test and measurement containing of the following 60-m sprint test, sprint fatigue test, maximum push up, one minute push up, beep test and V-sit. These are sequentially intended to measure speed, anaerobic endurance, upper extremity muscular endurance, abdominal muscular endurance, aerobic endurance, and flexibility. In addition, a different test was conducted using ANOVA technique to determine differences in physical conditions between starters and reserve players. The results suggested that generally the level of physical condition of PPLOP players is in good condition. However, the muscular endurance of the arms and shoulders requires an increase because the results are categorized as less. The significant difference in physical capacity between starters and reserve players was recorded only in the number of push ups (p <0.05) recorded. This research can be used as a reference for trainers in creating training programs and adopting the types of tests and measurements selected in this study as guidelines for physical measurement for basketball athletes.